Molecular Dynamics Simulation on Slippage Effect and Injection Capacity With Hydrophobic Nanoparticles Adsorption - Dong Zhang; Yuze Ye; Runnan Zhou; Peng Ye (Energy Science & Engineering)
ABSTRACT With the continuous exploitation of global oil and gas resources, the focus of oilfield development has gradually shifted to low‐permeability and tight reservoirs. Nowadays the nanofluid has become one of the most important methods to enhance oil recovery in low‐permeability reservoir since the wettability and fluid flow characteristics can be changed as hydrophobic nanoparticles are adsorbed on the surface. In this study, we focus on the fluid slip characteristics feature of nanoparticles adsorbed with different adsorption degrees through molecular dynamics methods. Our results show that the adsorption of hydrophobic nanoparticles on the wall induces a velocity slip effect. The fluid flows in a Cassie state in the micro‐channel, with a significant increase in density, velocity, and slip length. In addition, the velocity in the mainstream area is significantly greater than that near the wall. The fluid flow rate within the pore channel is maximized and the most optimal adsorption degree is around 65.08%. Meanwhile, this study provides not only of great significance for the microscopic mechanism of pressure reduction and injection enhancement technology by nanoparticles adsorbed, but also an efficient method in enhance oil recovery in low‐permeability oil reservoirs.